The Role of Project-Based Learning in Improving the Students’ English Writing Skill - Yuliana, Fitri; Zakariyah, Yogi Aldias (Proceeding International Conference on Religion, Science and Education, 2024)
Writing becomes one of the most difficult skill to be experted by the students in especially in high school levels. Therefore, Project Based-Learning is offered to solve the difficulties that were faced by the students in writing especially in 21st century learning which includes 4C (Communication, Collaboration, Critical Thinking, and Creativity). Some experts believe that Project Based-Learning can help the students to develop their writing skills through the projects that given by the teacher. This research reports on the implementation of Project Based-Learning in teaching writing especially narrative text. The objectives of this research are to describe the improvement of the student’s writing skill through Project Based-Learning and to describe the students’ attitudes in learning English writing skill through Project Based-Learning. This research uses qualitative method and classroom action research as a research design. The participants of the research were 21 students of tenth grade of MA Diponegoro Yogyakarta. The collected data were obtained through observation, writing test, and interview. The data were analysed based on triangulation. As result, it was found that the implementation of Project Based-Learning in teaching writing worked well. It could be seen from the student’s reponses and development during the implementation of this method. They showed an improvement especially from their post-test scores. Design Project Based Learning is suitable to be using Implementation in KBM especially improving students English writing skill. PBL could help the students to learn writing well, the students could enjoy the learning activities. On the other hand, this project developed the writing skill of the students.